Influences of Media Compositions on Characteristics of Isolated Bacteria Exhibiting Lignocellulolytic Activities from Various Environmental Sites - Gong, Gyeongtaek; Lee, Sun-Mi; Woo, Han Min; Park, Tai Hyun; Um, Youngsoon (Humana Press, Inc., 2017)
Efficient isolation of lignocellulolytic bacteria is essential for the utilization of lignocellulosic biomass. In this study, bacteria with cellulolytic, xylanolytic, and lignolytic activities were isolated from environmental sites such as mountain, wetland, and mudflat using isolation media containing the combination of lignocellulose components (cellulose, xylan, and lignin). Eighty-nine isolates from the isolation media were characterized by analyzing taxonomic ranks and cellulolytic, xylanolytic, and lignolytic activities. Most of the cellulolytic bacteria showed multienzymatic activities including xylanolytic activity. The isolation media without lignin were efficient in isolating bacteria exhibiting multienzymatic activities even including lignolytic activity, whereas a lignin-containing medium was effective to isolate bacteria exhibiting lignolytic activity only. Multienzymatic activities were mainly observed in Bacillus and Streptomyces, while Burkholderia was the most abundant genus with lignolytic activity only. This study provides insight into isolation medium for efficient isolation of lignocellulose-degrading microorganisms.